Injuries to both anterolateral ligament and Kaplan fiber of the iliotibial band do not increase preoperative pivot-shift phenomenon in ACL injury - Takeo Tokura; Kanto Nagai; Yuichi Hoshino; Shu Watanabe; Noriyuki Kanzaki; Kyohei Nishida; Takehiko Matsushita; Ryosuke Kuroda (Elsevier, 2024)
Background: To assess the incidence of anterolateral ligament (ALL) and Kaplan fiber of the iliotibial band (KF) injuries in patients with acute anterior cruciate ligament (ACL) injury on magnetic resonance imaging (MRI), and to investigate the association between these injuries and the magnitude of preoperative pivot-shift test. Method: One-hundred and five patients with primary ACL injury were retrospectively reviewed. ALL injury and KF injury were assessed by preoperative MRI, and subjects were allocated into four groups: Group A, neither injury; Group B, only ALL injury; Group C, only KF injury; Group D, simultaneous ALL and KF injuries. Before ACL reconstruction, tibial acceleration during the pivot-shift test was measured by an electromagnetic measurement system, and manual grading was recorded according to the International Knee Documentation Committee (IKDC) guideline. Results: In MRI, the ALL was identified in 104 patients (99.1%) and KF in 99 patients (94.3%). ALL and KF injuries were observed in 43 patients (43.9%) and 23 patients (23.5%), respectively. Patient distribution to each group was as follows; Group A: 43 patients (43.9%), Group B: 32 patients (32.7%), Group C: 12 patients (12.2%), Group D: 11 patients (11.2%). No significant differences were observed in tibial acceleration, and manual grading among the four groups. Conclusion: Simultaneous injury to both ALL and KF was uncommon, and preoperative pivot-shift phenomenon did not increase even in those patients. The finding suggests that the role of ALL and KF in controlling anterolateral rotatory knee laxity may be less evident in the clinical setting compared to a biomechanical test setting.